Design and fabricate of secured LCD remote control holder in UMP Pekan lecture room - Faris Syafiq, Zakaria (2010)
This report shows the design and fabrication of a secure LCD remote control holder. The objective of the report is to design and fabricate a secure LCD remote control holder. This report also describes the remote holder products which are available around the world with its safety criteria. Design generation is showed and solid three dimensional structures modelling of the remote control holder was developed with computer aided design software. This report also explains the fabrication process that is needed for this project. Material that is being used in this project is zinc sheet metal and mild steel bar, shaft and hollow shaft. The problems encountered during completion of this project are also show in the report. An idea of improvement for the remote control holder is also provided to further improve the remote control holder. The expected result for this project can solve the entire stated problem statement.